Clinical Application of Microsurgery Using the Cerebellar Medulla Fissure Approach in Severe Ventricular Hemorrhage with Casting of the Fourth Ventricle and Its Influence on Neurological Recovery - Feng Gao (Hindawi Limited, 2021)
Objective. To investigate the clinical application of microsurgery using the cerebellar medulla fissure approach in severe ventricular hemorrhage with casting of the fourth ventricle and its effect on neurological recovery. Methods. A total of 80 patients with severe intraventricular hemorrhage accompanied by casting and dilation of the fourth ventricle who were admitted to the neurosurgery department between July 2019 and December 2020 were randomly divided into an observation group and a control group, with 40 patients in each group. The drainage tube extubation time and length of hospital stay of the two groups were compared. The 3-day hematoma clearance of the two groups was observed. Postoperative consciousness was evaluated by GCS, and the patients’ recovery was evaluated by GOS at three months. The activities of daily living (ADL) scores of the two groups were compared to evaluate patients’ postoperative self-care ability. The incidence of postoperative complications in the two groups was collected. Independent risk factors for poor prognosis were analyzed by logistics regression. Results. The postoperative hospitalization time and the drainage tube extubation time in the observation group were significantly lower than those in the control group. The ratio of hematoma clearance ≥90% in the observation group was significantly higher than that of the control group. Postoperative GCS scores and GOS scores in the observation group were significantly higher than those of the control group. The rate of postoperative complications in the observation group was significantly lower than that of the control group. The rate of good ADL grading in the observation group was significantly higher than that in the control group. Age and surgical method were independent risk factors for poor prognosis. Conclusion. Microsurgery using the cerebellar medulla fissure approach can effectively improve the condition of severe ventricular hemorrhage with casting of the fourth ventricle and promote the recovery of patients’ neurological function.